EVOLUTION OF THE PROTAGONIST IN VASYL PACHOVSKYI’S DRAMATURGY - Верлата, А. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights the specificity of the main characters’ creation in Vasyl Pachovskyi’s plays «The Dream of Ukrainian Night», «The Sun of the Ruin», «The Sphinx of Europe», «Prince Roman the Great», and «Hetman Mazepa». The primary focus of the article is on the main psychological types of the plays and their part in the expression of the dominant ideas in these works. The realization of modernistic tendencies in the creation of the characters is considered.